Nanocell：an Aggregation Solution of TD-LTE and WLAN - Xi Cao; Ning Yang; Tao Sun; Guangyi Liu; Hui Deng (Dianxin kexue)
The rapid development of mobile internet and explosive growth of wireless data traffic especially for indoor scenarios，bring forward various challenges to mobile network operators. To achieve an aggregation of TD-LTE small cell and WLAN，the two types of hotspot and indoor coverage technologies，taking full advantage of the available WLAN site and its backhaul，offer the capability to offload the macro cell traffic and reduce operators’ network OPEX and CAPEX. The concept of Nanocell and its end-to-end solution for the whole network was introduced，aiming to combine the TD-LTE industry and WLAN industry effort，to make arduous efforts to meet the subscriber’s demand for data traffic in future and to maintain a healthy mobile industry.